Does depression co-occur within households? The moderating effects of financial resources and job insecurity on psychological contagion. (September 2022) - Kristensen, Thomas Borup; Pfeffer, Jeffrey; Dahl, Michael S.; Holm, Morten; Feldhues, Melanie Lucia
Abstract: The empirically related psychopathologies of stress and depression exact an enormous economic toll and have many physical and behavioral health effects. Most studies of the effects of stress and depression focus on their causes and consequences for a single, focal individual. We examine the extent to which depression, as indicated by filling antidepressant prescriptions (SSRI and Benzodiazepines), co-occurs across spouses, constituting a negative spillover effect. To better understand the conditions that affect within-household contagion of depression, we examine whether the stress and uncertainty occasioned by job change and financial stress (net worth) increases spillover effects among spouses. We use panel data from various Danish administrative registers from the year 2001–2015 with more than 4.5 million observations on more than 900, 000 unique individuals and their spouses from Danish health registers. Spouses in a household with their partner using antidepressants have a 62.1% higher chance of using antidepressants themselves, with the one year lagged effect being 29.3% and a two-year lagged effect of 15.1%. The effects become larger by 14.8% contemporaneously and 20% in the two-year lagged model if the focal individual changed employers. There was also a substantively unimportant effect of lower financial wealth to increase inter-spousal contagion.